2018
DOI: 10.5586/asbp.3574
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic landscape of Dendrobium huoshanense and its genes related to polysaccharide biosynthesis

Abstract: Dendrobium huoshanense has long been used to treat various diseases in oriental medicine. In order to study its gene expression profile, transcripts involved in the biosynthesis of precursors of polysaccharides, as well as mechanisms underlining morphological differences between wild and cultivated plants, three organs of both wild type and cultivated D. huoshanense were collected and sequenced by Illumina HiSeq4000 platform, yielding 919,409,540 raw reads in FASTQ format. After Trinity de novo assembly and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Mannose is one of the important components in D. huoshanense polysaccharide and Han et al have explored six related genes in mannose biosynthetic pathway 22 . In our study, ten related genes from fructose and mannose metabolism have been explored.…”
Section: Identification Of Degs In Polysaccharide and Flavonoid Biosymentioning
confidence: 99%
See 1 more Smart Citation
“…Mannose is one of the important components in D. huoshanense polysaccharide and Han et al have explored six related genes in mannose biosynthetic pathway 22 . In our study, ten related genes from fructose and mannose metabolism have been explored.…”
Section: Identification Of Degs In Polysaccharide and Flavonoid Biosymentioning
confidence: 99%
“…Previous work focused on identification and analysis glycosyltransferases (GTs) in polysaccharides biosynthesis 20 . Besides GTs, some metabolic pathways such as fructose and mannose metabolism may also participated in polysaccharides biosynthesis 21,22 . However, the biosynthesis mechanisms and metabolic pathways of polysaccharides have been not explored detailly in D. huoshanense.In China, the stem of Dendrobium is a traditional edible and medicinal part 2 .…”
mentioning
confidence: 99%
“…Annotated as “GTP-mannose-1-phosphate guanyltransferase” from deep transcriptomic data of D. huoshanense [ 13 ], the full-length DhGMPP cDNA (1,867 bp) was amplified and sequenced. DhGMPP (accession no.…”
Section: Resultsmentioning
confidence: 99%
“…GDP-mannose pyrophosphorylase gene ( DhGMPP ) is a key factor to yield GDP-mannose and ultimately DhPs. By digging into D. huoshanense RNA-Seq data [ 13 ], we cloned a DhGMPP which was then functionally expressed in Escherichia coli . The function of DhGMPP recombinant protein to catalyze the reaction of α -D-mannose-phosphate and GTP to form GDP-D-mannose was also characterized ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…It also shows that wild D. huoshanense has the highest nutritional value, followed by indoors. Numerous studies have shown that the cloning and expression of key enzyme genes in plant secondary metabolic pathways can increase the yield of secondary metabolites in plants, understand their biosynthetic pathways and regulatory mechanisms and regulate key genes affecting secondary metabolites (Han et al 2018). To increase its expression, thereby promoting the production of the desired product.…”
Section: Discussionmentioning
confidence: 99%